Interrogation of allelic chromatin states in human cells by high-density ChIP-genotyping - Light, Nicholas (Landes Bioscience, 2014)
Allele-specific (AS) assessment of chromatin has the potential to elucidate specific cis-regulatory mechanisms, which are predicted to underlie the majority of the known genetic associations to complex disease. However, development of chromatin landscapes at allelic resolution has been challenging since sites of variable signal strength require substantial read depths not commonly applied in sequencing based approaches. In this study, we addressed this by performing parallel analyses of input DNA and chromatin immunoprecipitates (ChIP) on high-density Illumina genotyping arrays. Allele-specificity for the histone modifications H3K4me1, H3K4me3, H3K27ac, H3K27me3, and H3K36me3 was assessed using ChIP samples generated from 14 lymphoblast and 6 fibroblast cell lines. AS-ChIP SNPs were combined into domains and validated using high-confidence ChIP-seq sites. We observed characteristic patterns of allelic-imbalance for each histone-modification around allele-specifically expressed transcripts. Notably, we found H3K4me1 to be significantly anti-correlated with allelic expression (AE) at transcription start sites, indicating H3K4me1 allelic imbalance as a marker of AE. We also found that allelic chromatin domains exhibit population and cell-type specificity as well as heritability within trios. Finally, we observed that a subset of allelic chromatin domains is regulated by DNase I-sensitive quantitative trait loci and that these domains are significantly enriched for genome-wide association studies hits, with autoimmune disease associated SNPs specifically enriched in lymphoblasts. This study provides the first genome-wide maps of allelic-imbalance for five histone marks. Our results provide new insights into the role of chromatin in cis-regulation and highlight the need for high-depth sequencing in ChIP-seq studies along with the need to improve allele-specificity of ChIP-enrichment.